1985
DOI: 10.1007/bf01992775
|View full text |Cite
|
Sign up to set email alerts
|

The importance of grazing food chain for energy flow and production in three intertidal sand bottom communities of the northern Wadden Sea

Abstract: In three intertidal sand bottom communities of the "K6nigshafen" (Island of Sylt, North Sea), the biomass production and respiration of phytobenthos, phytoplankton, macrozoobenthos, and in situ community metabolism were measured monthly during 1980. The study sites were characterized by different communities (Nereis-Corophium-belt, seagrass-bed, Arenicola-flat) and by a high abundance of the mollusc Hydrobia ulvae. Benthic diatoms are the major constituents of plant biomass in the Arenicola-flat. In this commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 66 publications
3
47
0
Order By: Relevance
“…5). A similar seasonal pattern of GPP has previously been observed at the same two locations (Asmus & Asmus, 1985). Temperature appeared to be a significant controlling factor for GPP at the muddy site (Table 3), while overall control at the two sandy sites seems more complex clue to simultaneous influence of biotic (e.g.…”
Section: Microbenthic Primary Production and Respirationsupporting
confidence: 83%
See 2 more Smart Citations
“…5). A similar seasonal pattern of GPP has previously been observed at the same two locations (Asmus & Asmus, 1985). Temperature appeared to be a significant controlling factor for GPP at the muddy site (Table 3), while overall control at the two sandy sites seems more complex clue to simultaneous influence of biotic (e.g.…”
Section: Microbenthic Primary Production and Respirationsupporting
confidence: 83%
“…Grant, 1986), where incubations are carried out at prevailing temperature and light conditions. Although differences between fluxes obtained by the latter approaches in the Wadden Sea and our laboratory core experiments occur, the general pattern and flux rates of 02 and DIN are of similar and comparable magnitude (van Es, 1982;Hargrave et al, 1983;Henriksen et al, 1984;Asmus & Asmus, 1985;Therkildsen & Lomstein, 1993). However, flux rates obtained by the use of large-scale flumes and similar constructions, which enclose entire sub-systems under the influence of all prevailing physical and chemical factors, may differ considerably (Asmus et al, in prep).…”
Section: Methodological Considerationsmentioning
confidence: 57%
See 1 more Smart Citation
“…Data of the microalgal composition of the Arenicola-flat are already given in Asmus (1982), and the annual course of total microalgal biomass in the three communities has been described in Asmus & Asmus (1985). Here we present annual courses of cell numbers, size spectra, species composition of benthic microalgae in the seagrass-bed and in the Nereis-Corophium-belt, cluster analyses and dendrograms.…”
Section: Cluster Analysismentioning
confidence: 96%
“…Cad6e & Hegeman (1974) found values of 100 (+ 40) g C/m2/year for the benthic primary production -a value that is supported by results from the Dollard estuary presented by van Es (1977), who estimated a benthic primary production of 116 g C/m2/year. Asmus & Asmus (1985) found values of 150 g C/m2/year for the benthic primary production in K6nigshafen, and Bruns et al (1995) found a mean value of 111 (+ 35) g C/m2/year computed for the whole of Sylt-Romo tidal basin. Furthermore, van Es (1977) found a pelagic primary production of 7.5 g C/m2/year.…”
Section: Primary Productionmentioning
confidence: 97%